An Extension of the Product Acceptance Determination for One‐Sided Process with Multiple Characteristics. (16th March 2012) - Pearn, W. L.; Wu, C. H.; Hung, H. N.; Kao, C. M.
Abstract : In statistical quality control, product acceptance determination is an important problem for producer and consumer. In practical, particularly more than one quality characteristic must be simultaneously considered to improve the product quality because of the product design. In this article, we investigate the lot sentencing problem for normally distributed process with one‐sided specification and multiple characteristics. We not only provide a simple procedure to help practitioners make reliable decision easily but also tabulate the required sample size and the corresponding critical acceptance value for various producer's and consumer's risks with the capability requirements AQL (acceptable quality level) and LTPD (lot tolerance percent defective). Copyright © 2012 John Wiley & Sons, Ltd.